Drug resistance of M. Tuberculosis isolated from patients with HIV infection seen at an AIDS Reference Center in São Paulo, Brazil - Pinto, Walkyria P; Hadad, David J; Palhares, M. Cecília A; Ferrazoli, Lucilaine; Telles, M. Alice S.; Ueki, Sueli Y.M.; Santos, Márcia T. F.; Placco, Ana L. N.; Sauaia, Naim; Palac, Moisés (Revista do Instituto de Medicina Tropical de São Paulo, 1996)
M. tuberculosis-positive cultures were obtained from 228 patients seen in our service and drug sensitivity assays were carried out from January 1992 to December 1994. A survey of the medical records of these patients showed resistance to one or more drugs in 47 (20.6%), 25 of whom (10.9%), who reported previous treatment, were considered to have acquired resistance. Among the antecedents investigated, only previous treatment and alcoholism were the factors independently associated with the occurrence of resistance. The survival of patients with resistant strains was lower than that of patients attacked by non-resistant M. tuberculosis. We conclude that in the present series M. tuberculosis resistance to tuberculostatic agents was predominantly of the acquired type.